1998
DOI: 10.1258/0956462981922764
|View full text |Cite
|
Sign up to set email alerts
|

Vulvovaginal candidiasis in female sex workers

Abstract: Vulvovaginal candidiasis is a frequent inflammatory process in women but it has not been widely studied in female sex workers (FSWs). To estimate the frequency of Candida species infection in FSWs and to identify related risk factors and clinical findings, we carried out a retrospective study of 1923 FSWs over 11 years. We also performed a prospective study of 163 consecutive FSWs with a history of candidiasis during a 4-year period. Candida species were isolated in 1967 samples (18.5% of the total). Candida a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 20 publications
3
22
1
1
Order By: Relevance
“…Similarly, a prospective case± control study of 163 Spanish female sex workers followed up over a period of four years found no statistically signi® cant association between RVVC and the use of tight-® tting clothing and synthetic underwear 180 .…”
Section: Clothingmentioning
confidence: 98%
“…Similarly, a prospective case± control study of 163 Spanish female sex workers followed up over a period of four years found no statistically signi® cant association between RVVC and the use of tight-® tting clothing and synthetic underwear 180 .…”
Section: Clothingmentioning
confidence: 98%
“…In a study involving 163 female sex workers with histories of candidal vaginosis over a 4-year period in Spain, Candida species were isolated in 1,967 samples (18.5% of the total), of which C. albicans accounted for 89.3% of isolates while C. parapsilosis was rarely identified (1.2%) (204). Lower incidences of C. albicans were found among pregnant Tanzanian women with vaginal candidiasis (66.2%), although C. parapsilosis was still isolated rarely (2.2%) (187 (195).…”
Section: Parapsilosis Remains An Infrequent Cause Of Fungal Vulvovmentioning
confidence: 99%
“…albicans is responsible for most cases of VVC (2,3); the rest are caused by non-albican species of Candida which include C. glabrata, C. krusei, and C. tropicalis. Non-albican species of Candida have demonstrated decreased susceptibility to commonly used antifungal agents (5).…”
Section: Introductionmentioning
confidence: 99%